Building student engagement through co-production and curriculum co-design in public administration programmes. Issue 3 (October 2021) - Elliott, Ian C; Robson, Ian; Dudau, Adina
Public administration as a field of work and study offers a theoretically rich yet practical tool to enact student engagement and the ideal of students-as-partners: the principles of service co-creation. Public administration, as an interdisciplinary and applied field, promoting and reflecting democratic principles, is a good source of tools for practice. As such we expect it to be particularly suitable for curriculum co-design principles. Our research sets potential benefits and challenges in facilitating a co-designed curriculum for public administration programmes. In doing so we make the case for more co-design and co-production of teaching as a tool to achieve enhanced understanding of these concepts and greater student engagement.